Analysis of the fluidized bed combustion behavior of Quercus ilex char. (25th April 2015) - Pereira, Carlos C.; Pinho, Carlos
Abstract: Because of the high content of alkaline metals, biomass has very reactive ashes and these have a strong impact upon pyrolysis and combustion phenomena. From the study of the evolution with the combustion temperature, of the kinetic and diffusive data of several wood chars, it was found that the Quercus ilex (holm oak) char had an unexpected evolution of the heterogeneous phase reaction rate constant. Scanning electronic microscopy analysis of the ashes and thermogravimetric analysis of the char where performed, and the results shown that close to 750 °C there is a loss of mass associated with the release of inorganic matter, especially potassium and phosphorus, which have a known influence on the combustion process and the subsequent kinetic data collection. Highlights: Fluidized bed combustion of biomass. Combustion behavior of holm oak char. Influence of alkaline components on char combustion kinetic data.